Antibacterial Potency from Ethanol Extract Leaves of Kluwih (Artocarpus camansi Blanco) against Shigella dysenteriae and Bacillus subtilis - Sogandi, Sogandi; Amelia, Amelia (Jurnal ILMU DASAR, 2020)
Gastrointestinal infection is a common infection in Indonesia. Many bacteria could cause gastrointestinal disorder, including Shigella dysenteriae and Bacillus subtilis. Currently, they are treated using chemical and traditional drugs. One of the common pants in Indonesia is Kluwih (Artocarpus camansi). The objective our study to determine antibacterial activity and inhibitory mechanism of Kluwih leaf extract against pathogenic bacteria which cause gastrointestinal infection, i.e. Shigella dysenteriae and Bacillus subtilis. The extraction process used maceration technique using 96% ethanol solvent and the antibacterial activity was studied using agar diffusion method. The research result showed that Kluwih leaf extract had inhibitory power with KHM (minimum inhibitory concentration) value of 25% against S. dysenteriae and 6.25% against B. subtilis. The present study also revealed that Kluwih leaf was suspected to have inhibitory activity against bacteria by making holes in the membrane of bacterial cell, leading to the release of nucleic acid and protein and cell death.Keywords: antibacterial, Artocarpus camansi, kluwih, Shigella dysenteriae, Bacillus subtilis.